Size and material of model parasitic eggs affect the rejection response of Western Bonelli's Warbler Phylloscopus bonelli. (January 2017) - Roncalli, Gianluca; Ibáñez‐Álamo, Juan Diego; Soler, Manuel
Abstract : Given the high costs of brood parasitism, avian hosts have adopted different defences to counteract parasites by ejecting the foreign egg or by deserting the parasitized nest. These responses depend mainly on the relative size of the host compared with the parasitic egg. Small hosts must deal with an egg considerably larger than their own, so nest desertion becomes the only possible method of egg rejection in these cases. The use of artificial model eggs made of hard material in egg‐recognition experiments has been criticized because hard eggs underestimate the frequency of egg ejection. However, no available studies have investigated the effect of softer material. Here, we test the potential effect of size of dummy parasitic eggs in relation to egg‐rejection behaviour (egg ejection and nest desertion rates) in Western Bonelli's Warbler Phylloscopus bonelli, a small host, using plasticine non‐mimetic eggs of three different sizes. In addition, we tested the potential effect of material, comparing ejection and desertion responses between real and plasticine eggs. As predicted, small eggs were always ejected, whereas nest desertion occurred more frequently with large eggs, thus suggesting that nest desertion occurs because of the constraints imposed by the large eggs. We found that plasticine may misrepresent the responses to experimental parasitism, at least in small host species, because this material facilitates egg ejection, provoking a decrease in nest desertion rate. Thus, particular caution is needed in the interpretation of the results in egg‐rejection experiments performed using dummy eggs made of soft materials.